LEADING COMMODITIES AND COMPETITIVENESS AGRICULTURAL SECTOR OF WEST PASAMAN DISTRICT - Syahrial; Angelia Leovita; Haslinda Simangunsong (Universitas Perjuangan Tasikmalaya, 2024)
The Agricultural Sector is the dominant business sector in gross regional domestic product (GRDP) in improving the economy of West Pasaman Regency. This research aims to 1) analyze essential superior commodities, 2) analyze the economic competitiveness of the agricultural sector in West Pasaman Regency, and 3) analyze trends in superior commodities in the future. The analytical tools used are Location Quotient, Localization Quotient, Specialization Quotient, Shift Share, and Dynamic Location Quotient. The results showed that 1) West Pasaman Regency had 40 percent of the 15 commodities base commodities, 2) the food crops, horticulture, and plantation subsector had competitors with increased growth, and 3) there are 47 percent of the 15 commodities with potential and future trends. The West Pasaman Regency government must also look at what factors support several commodities, such as commodities that are not basic, not developed, or underdeveloped, so that these commodities in the future can compete and become prime commodities in the region so that they can encourage regional growth and economics.